Literature in the language classroom : a resource book of ideas and activities - Collie, Joanne; Slater, Stephen (New York : Cambridge University Press, 1987)
Presents a comprehensive resource guide for English-language teachers that features a collection of techniques and activities for integrating literature work with language reading.
Includes bibliographical references (p. 263) and index.
Professional
Keywords: Philology -- Study and teaching; Language and languages -- Study and teaching